(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This article analyzes the conception of the performance Abismo (2022), by the Midiactors group, through the lens of practice-based research in the performing arts. It investigates the work’s transition from a multimedia logic to an intermedia structure, where light and projection become inseparable from the dramaturgy. The research articulates Loïe Fuller’s legacy with contemporary technologies within the site-specific context of the Museum of the Mines School (UFOP). The results demonstrate that the hybridization between the body and digital media establishes a phenomenology of perception that transcends technical function, converting lighting into a vector of subjectivity and immersion.